Outdoor Adventure Program Builds Confidence and Competence to Help New Graduate RNs Become "Everyday" Leaders at the Point of Care. Issue 1 (January 2015) - Greer-Day, Susan; Medland, Jackie; Watson, Lynn; Bojak, Sarah
<x xml:space="preserve">Abstract</x> A nontraditional approach to leadership development promoted successful transition of new graduate RN residents to professional nurses. Utilizing an outdoor adventure program increased nurses' feelings of competence by boosting their confidence, facilitating an environment where leadership at the bedside became an ingrained part of their nursing practice. RN residents at a Midwestern medical center represented only 17% of the nursing population but reshaped the culture of the entire organization by becoming dynamic "everyday" leaders.